Image of Lord Brahma on the Shikhara - Temples of India Project Team (Jio Institute, 2024)
On one facet of the shikhara (superstructure), Brahma sits in divine contemplation. Portrayed with three faces and four arms, Brahma holds a shruka (sacrificial ladle) in his upper left hand, while his upper left-hand holds a pustaka (sacred text). His lower right hand is in the varada hasta gesture, while his lower left-hand clasps a kamandalu (water pot), representing purity and sustenance. He is adorned with a jatamukuta (crown of matted hair) and jewellery. His long eyes, straight nose, and full lips convey a sense of timeless grace, while his long beard adds to his aura. Bare-chested, Brahma wears a broad yajnopavita (sacred thread), symbolizing his connection to spiritual and ritualistic wisdom.